Partikularitas dan Universalitas: Soteriologi Paulus di Roma 3 - Airey, Aser; Heryanto, Doni; Oko, Oral (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
This research discusses the theological understanding of how salvation works particularly for God’s chosen people, as well as the universality of the offer of salvation for all humanity. Romans 3 serves as a significant foundation for this understanding, where Paul explains that all humans have fallen into sin and need God’s grace through faith in Jesus Christ. The purpose of this study is to deeply analyze the role of grace in salvation and how the theological views of particular and universal salvation can be understood in light of Paul’s soteriology. By referring to Romans 3:22-23, this research also seeks to explain the connection between justification by faith and the universality of sin, which necessitates salvation through Christ. The method used in this research is a descriptive qualitative method with an expository approach to the biblical text, particularly the letter to the Romans. Textual analysis is carried out to explore the theological meaning of the concept of salvation in the context of Paul’s teachings. The results of the study show that while Paul speaks about the election of the chosen people, he still affirms that salvation is offered to all humanity through faith. Thus, Paul’s understanding of salvation unites both particular and universal aspects in the redemptive work of Christ. Penelitian ini membahas latar belakang pemahaman teologis tentang bagaimana keselamatan bekerja secara partikular bagi umat pilihan Allah, serta universalitas tawaran keselamatan bagi semua manusia. Roma 3 menjadi landasan penting dalam pemahaman ini, di mana Paulus menjelaskan bahwa semua manusia telah jatuh ke dalam dosa dan membutuhkan anugerah Allah melalui iman kepada Yesus Kristus. Tujuan dari penelitian ini adalah untuk menganalisis secara mendalam peran kasih karunia dalam keselamatan dan bagaimana pandangan teologi partikular dan universal dapat dipahami dalam terang soteriologi Paulus. Dengan mengacu pada Roma 3:22-23, penelitian ini juga berusaha menjelaskan keterkaitan antara pembenaran oleh iman dan universalitas dosa yang menuntut keselamatan melalui Kristus. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif dengan pendekatan eksposisi teks Alkitab, khususnya surat Roma. Analisis teks dilakukan untuk mengeksplorasi makna teologis dari konsep keselamatan dalam konteks ajaran Paulus. Hasil penelitian menunjukkan bahwa Paulus, meskipun berbicara tentang pemilihan umat pilihan, tetap menegaskan bahwa keselamatan ditawarkan kepada semua manusia melalui iman. Dengan demikian, pemahaman keselamatan Paulus menyatukan aspek partikular dan universal dalam karya penebusan Kristus.